Geriatric dentistry, teaching and future directions. (March 2015) - Slack‐Smith, LM; Hearn, L; Wilson, DF; Wright, FAC
Abstract: Background: Many nations are facing a demographic shift in the age profile of their population, leading the World Health Organization to a 'Call for Public Health Action' on the oral health of older people. Methods: A search of the literature relevant to geriatric dentistry teaching was undertaken using MEDLINE, Web of Science, Eric and Psychlit. A search of dental professional school websites in Australia and policy and international practice documents was undertaken. Results: The international literature describes requirements for geriatric dentistry courses and various approaches to teaching, including didactic teaching, practical experiences and external placements. Challenges are identified in the area of geriatric dental education. Educational institutions (with others) have an obligation to lead change, yet there appears to be little formal recognition in Australian dental curricula of the need to develop quality education and research programmes in geriatric dentistry. Conclusions: Internationally, the inclusion of geriatrics within dental curricula has been the subject of consideration since the 1970s. The current evidence indicates that geriatrics/gerodontology is not a significant component of dental curricula. Given the projected age distribution in many countries, the need for implementation of dental curriculum content in the area of geriatrics/gerodontology is evident.